2010
DOI: 10.1530/eje-10-0427
|View full text |Cite
|
Sign up to set email alerts
|

Number of autoantibodies and HLA genotype, more than high titers of glutamic acid decarboxylase autoantibodies, predict insulin dependence in latent autoimmune diabetes of adults

Abstract: Objective: In latent autoimmune diabetes of adults (LADA), the progression into insulin-dependent diabetes is usually faster than in type 2 diabetes (T2D) but the factors influencing this progression are not completely known. In this study, we searched for sensitive markers associated with early development of insulin dependence. Design: The screening of 5568 T2D patients for glutamic acid decarboxylase autoantibodies (GAD65Ab) identified 276 LADA patients (MZ131; FZ145) and in 251 of them, tyrosine phosphatas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
83
2
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(96 citation statements)
references
References 32 publications
10
83
2
1
Order By: Relevance
“…On the other hand, other groups do not rely entirely on high anti-GAD65 titres, in order to predict the progression of LADA. Instead, strong predictors are considered the co-existence of positive autoantibodies and both HLA-DRB1 and HLA-DQB1, while, traits including female gender and low BMI and are highly likely to predict insulin requirement within 4 years post-diagnosis [43] . In mid-1990s, two independent groups will add an additional T1D specific autoantigen to the ICAs reactivity panel, the insulinoma antigen 2 (IA-2), a transmembrane molecule belonging to the family of protein tyrosine phosphatases [44][45][46] .…”
Section: At Thementioning
confidence: 99%
“…On the other hand, other groups do not rely entirely on high anti-GAD65 titres, in order to predict the progression of LADA. Instead, strong predictors are considered the co-existence of positive autoantibodies and both HLA-DRB1 and HLA-DQB1, while, traits including female gender and low BMI and are highly likely to predict insulin requirement within 4 years post-diagnosis [43] . In mid-1990s, two independent groups will add an additional T1D specific autoantigen to the ICAs reactivity panel, the insulinoma antigen 2 (IA-2), a transmembrane molecule belonging to the family of protein tyrosine phosphatases [44][45][46] .…”
Section: At Thementioning
confidence: 99%
“…During the early phase of disease, individuals with LADA can retain good metabolic control through diet alone or by taking oral hypoglycemic drugs, and this state can last from months to years. However, a percentage of LADA patients progress toward insulin requirement, indicating that LADA involves a slow and progressive loss of b-cells (5), although the factors influencing this progression are not completely known (6). The first evidence, demonstrating that a high GADA titer is a stronger predictor of insulin requirement than a general GADA positivity, was obtained from two studies with a limited number of LADA patients (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…UKPDS 25 reported, in a larger population of LADA patients, that high GADA titer was associated with a significant higher risk of insulin requirement only among subjects older than 55 years at diagnosis (1). Afterwards, conflicting results were reported in the literature; some studies demonstrated that a high titer of GADA was associated with a shorter insulin-free period (9,10,11), whereas others did not support this hypothesis (6,12).…”
Section: Introductionmentioning
confidence: 99%
“…While most type 1 diabetes (T1D) cases develop in pre-adolescence, late onset diabetes (LADA), may appear generally from 40-60 yr of age and is often confused with type 2 diabetes. The progression of diabetes symptoms may be responsible for 10-15% of diabetes related heart disease mortality especially in low income socio-economic groups which are at greatest risk for diabetes related health disparities in the U.S (Kobayashi et al 2006;Maioli, Puddu, and Pes 2006). Diagnosis and treatment of hyperglycemia is poor, as islet -cell destruction is completely asymptomatic until more than half of the approximately 1x10 6 pancreatic islets have been destroyed or inactivated (Tang et al 2006).…”
Section: Type 1 Diabetes Results From Genetic Predisposition and A Brmentioning
confidence: 99%